n = 1 ∑ 1 0 0 F n 2 n = 1 ∑ 1 0 0 F n 3 + n = 3 ∑ 1 0 0 F n F n − 1 F n − 2 = ?
Notation: F n denotes the n th Fibonacci number , where F 1 = F 2 = 1 and F n = F n − 1 + F n − 2 for n ≥ 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It can be proved geometrically that n = 1 ∑ x ( F n 3 ) = ( F x ) 2 F x + 1 − n = 3 ∑ x F n F n − 1 F n − 2 for all x ≥ 3
Rearranging we get n = 1 ∑ x ( F n 3 ) + n = 3 ∑ x F n F n − 1 F n − 2 = ( F x ) 2 F x + 1
It can also be shown geometrically that F x F x + 1 = n = 1 ∑ x ( F n 2 )
Therefore n = 1 ∑ x ( F n 3 ) + n = 3 ∑ x F n F n − 1 F n − 2 = ( F x ) n = 1 ∑ x ( F n 2 )
Rearranging we get n = 1 ∑ x ( F n 2 ) n = 1 ∑ x ( F n 3 ) + n = 3 ∑ x F n F n − 1 F n − 2 = F x
When x = 1 0 0 the equation is equal to F 1 0 0
Problem Loading...
Note Loading...
Set Loading...
k = 1 ∑ n F k F k + 1 F k + 2 = k = 1 ∑ n ( F k + 2 − F k + 1 ) F k + 1 F k + 2 = k = 1 ∑ n ( F k + 1 F k + 2 2 − F k + 1 2 F k + 2 ) = k = 1 ∑ n ( F k + 1 F k + 2 2 − F k + 1 2 ( F k + F k + 1 ) ) = k = 1 ∑ n ( F k + 1 F k + 2 2 − F k F k + 1 2 − F k + 1 3 ) = F n + 1 F n + 2 2 − F 1 F 2 2 − k = 1 ∑ n F k + 1 3 = F n + 1 F n + 2 2 − 1 − k = 2 ∑ n + 1 F k 3 = F n + 1 F n + 2 2 − k = 1 ∑ n + 1 F k 3
Therefore,
Q = ∑ k = 1 n F k 2 ∑ k = 1 n F k 3 + ∑ k = 3 n F k F k − 1 F k − 2 = ∑ k = 1 n F k 2 ∑ k = 1 n F k 3 + ∑ k = 1 n − 2 F k F k + 1 F k + 2 = F n F n + 1 ∑ k = 1 n F k 3 + F n − 1 F n 2 − ∑ k = 1 n − 1 F k 3 = F n F n + 1 F n 3 + F n − 1 F n 2 = F n F n + 1 F n 2 ( F n − 1 + F n ) = F n F n + 1 F n 2 F n + 1 = F n Note that k = 1 ∑ n F k 2 = F n F n + 1
For n = 1 0 0 , the answer is F 1 0 0 .